Standards and small and medium enterprises in Vietnam: the situational analysis and some policy implications - Nguyen Quynh Anh; Nguyen Thi Bich Phuong; Nguyen Van Hieu (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
The role of standards in fostering innovation within businesses is crucial, and this article delves into the current state and perspectives of small and medium-sized enterprises (SMEs) in applying standards to enhance productivity and innovation. The survey results of 152 enterprises show that the adoption of standards yields three notable benefits: ensuring product quality, expanding market access for enterprises, particularly in terms of exports, and providing societal advantages such as health safety, environmental protection, and consumer safeguarding. However, there are challenges associated with implementing standards, including the costs of meeting the standard requirements, modifying production processes, and intensifying monitoring efforts to ensure product compliance, especially concerning international standards. To support SMEs in engaging in global value chains, it is essential to reinforce the transparency and diversifying channels for disseminating information regarding trade measures and technical barriers. Additionally, there is a need for policies that support SMEs in meeting sustainability requirements, encourage the adoption of science and technology, and provide assistance programs to enhance productivity through innovation. These suggestions aim to empower SMEs and enable their participation in global value chains. Code: 23021001